Práticas alimentares de crianças de 6 a 12 meses e fatores maternos associados Feeding habits of children aged 6 to 12 months and associated maternal factors - Silvia Regina D. M. Saldiva; Maria Mercedes Escuder; Lenise Mondini; Renata B. Levy; Sonia I. Venancio (Elsevier, 2007)
OBJETIVOS: Identificar as práticas alimentares de crianças de 6 a 12 meses de idade e sua associação com fatores maternos. MÉTODOS: Trata-se de um estudo de delineamento transversal, no qual foram analisados os dados do Projeto Amamentação e Municípios de 2004, conduzido em 136 municípios do estado de São Paulo com 24.448 crianças. O padrão de consumo de alimentos foi avaliado segundo a freqüência de crianças que receberam leite materno e outros alimentos nas últimas 24 horas, e a probabilidade de consumo dos alimentos, nas faixas de idade, foi estimada por meio da análise de probitos. RESULTADOS: O consumo de alimentos revelou que 50% receberam leite materno, 77% outros tipos de leite, 63% mingau, 87% frutas, 78% sopas, 64% comida de panela, 58% comida com feijão e 36% sopa ou comida com carne. A probabilidade de a criança, aos 6 meses de idade, consumir sopas é elevada (78%), comida de panela é baixa (39%), e a probabilidade dela receber leite materno é de 59%, inferior aos outros leites (70%) e mingau (63%). Encontrou-se associação entre consumo de refeições lácteas e mães primíparas, que trabalhavam fora e com maior escolaridade. Semelhantes achados foram observados para consumo de sopas, acrescido à idade da mãe superior a 20 anos. O consumo de comida de panela associou-se a mães com menos de 20 anos, que não trabalhavam fora, com menor escolaridade e multíparas. CONCLUSÃO: Verificou-se consumo excessivo de alimentos líquidos e semi-sólidos e a necessidade do aconselhamento adequado em alimentação complementar, considerando idade, primiparidade, escolaridade e trabalho materno. OBJECTIVE: To identify the feeding practices of children aged 6 to 12 months of age and associated maternal factors. METHODS: This was a cross-sectional study analyzing data from the 2004 Breastfeeding and the Municipalities Project, which was implemented in 136 municipalities in the state of São Paulo, Brazil, with 24,448 children. The foods these children ate were profiled according to the number of children who had been given breastmilk and/or other foods during the previous 24 hours, and based on this data the probability of consumption of each food at each age was estimated by means of probit analysis. RESULTS: It was observed that 50% of the sample were being given breastmilk, 77% other types of milk, 63% porridge, 87% fruit, 78% soups, 64% the family meal, 58% meals including beans and 36% soup or meals containing meat. The probability of a 6-month-old child being given soup is elevated (78%), while for the family meal it is low (39%), and the probability of being fed breastmilk is 59%, lower than for other milks (70%) and than for porridge (63%). Associations were observed between milk-based meals and primiparous mothers, mothers employed outside the home and mothers who had spent longer in education. Similar findings were observed for soups, added to maternal age of more than 20 years. The family meal was associated with mothers under 20 years old, mothers who were not employed outside the home, mothers with fewer years' education and multiparous mothers. CONCLUSIONS: Excessive consumption was observed of liquid and semi-solid foods, suggesting that appropriate guidance on complementary feeding is needed, taking into account age, primiparity, education and employed mothers.